Applying Gamification Principles and Therapeutic Movement Sequences to Design an Interactive Physical Activity Game: Development Study - Hyungsook Kim; David Michael O'Sullivan; Seong Hee Chung (JMIR Publications, 2022)
BackgroundDepression is a severe illness that has accelerated with the spread of COVID-19 and associated lockdowns. As a result, reported physical activity has substantially decreased, further increasing depressive symptoms. ObjectiveThis study aims to explain the use of gamification principles to develop content for an interactive physical activity game for depression based on clinically proven depression diagnostic criteria. MethodsWe discuss related work in this field, the game design framework, the users' depression severity, how we customize the contents accordingly, the gradual progression of the game to match exercise principles, and user flow optimization. ResultsWe provide a brief description of each of the games developed, including instructions on how to play and design aspects for flow, audio, and visual feedback methods. Exergames (interactive physical activity-based games) stimulate certain physical fitness factors such as improving reaction time, endurance, cardiovascular fitness, and flexibility. In addition, the game difficulty progresses based on various factors, such as the user's performance for successful completion, reaction time, movement speed, and stimulated larger joint range of motions. Cognitive aspects are included, as the user has to memorize particular movement sequences. ConclusionsMental health issues are linked to behavior and movement; therefore, future physical activity-based interactive games may provide excellent stimulation for inducing user flow, while physical activity can help train various physical fitness factors linked to depression.